Sales and marketing integration: an exploratory study on the role of digital content strategy - Monti, Elisabetta; Ancillai, Chiara; Pascucci, Federica (Piccola Impresa / Small Business, 2021)
Despite the importance and the numerous benefits of sales-marketing integration, a significant gap between sales and marketing still exists. The literature has recently suggested that digital content marketing (DCM) might play a role in the sales-marketing integration in B2B companies. Notwithstanding the growing academic interest on DCM and its potential for the sales-marketing integration, we lack a thorough understanding of how the implementation of a DCM strategy triggers the mechanisms behind such an integration. We conduct a single case study to investigate the role of a DCM strategy in a B2B SME. The findings indicate that the DCM strategy enhances information sharing, structural linkages, customer orientation and power mechanisms. In doing so, we contribute to the literature by showing that a DCM strategy can effectively play a supporting role in the sales-marketing integration.